The Managing Director's Global Policy Agenda, Spring Meetings 2020 : Exceptional Times Exceptional Action. (Policy Papers; Policy Paper ;, 2020)
Managing Director Kristalina Georgieva's Global Policy Agenda, Exceptional Times, Exceptional Action, highlights three priorities for policymakers around the world: protect lives, protect livelihoods, and plan for the recovery. She Says 'The reality is that anyone's fight against the #COVID-19 virus is everyone's fight. More than ever we need global solidarity, a common resolve, and coordinated international efforts. And with so many countries short on resources, we need to give more support to those most in need,'.